If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-2)-3=-5(-4x+3)-8x
We move all terms to the left:
3(x-2)-3-(-5(-4x+3)-8x)=0
We multiply parentheses
3x-(-5(-4x+3)-8x)-6-3=0
We calculate terms in parentheses: -(-5(-4x+3)-8x), so:We add all the numbers together, and all the variables
-5(-4x+3)-8x
We add all the numbers together, and all the variables
-8x-5(-4x+3)
We multiply parentheses
-8x+20x-15
We add all the numbers together, and all the variables
12x-15
Back to the equation:
-(12x-15)
3x-(12x-15)-9=0
We get rid of parentheses
3x-12x+15-9=0
We add all the numbers together, and all the variables
-9x+6=0
We move all terms containing x to the left, all other terms to the right
-9x=-6
x=-6/-9
x=2/3
| -17–13q=-16q+10 | | 2/3z=41/4 | | 3v=9/7 | | 6(y-1)-2=-4(-6y+3)-8y | | (9x+72)=(4x+112) | | 5x+22=8x+4 | | 2y-6-3y=-7 | | -5x11=6(2x-10) | | -19=9v-1 | | -8d+15=55 | | 12=4/5v | | 1/9y+5=-7 | | 21=1-2x | | -5g=1=7+2g | | -2x-16=4(x-7) | | -32=-5c+13c | | 2+4v=22 | | 8j+1=3j-19 | | Y=(x+2)² | | -20-14=v | | -18d+15=55 | | -140=18+4(5y−2) | | 2/x+5/1/3=19 | | -4w+2(w+8)=30 | | 4.2x=1.4x=2.1 | | 10-5+y)-3=17 | | 8+3p=11 | | -35-4x=37-x | | 2/x+5/3=19 | | 6-4x=6x-8x+100 | | 1+2v=13 | | 3-x+7*2=9 |